“Literally Everything I Utter Is a Metaphor”: Thought Unhinged in The Water Cure and Percival Everett by Virgil Russell, by Percival Everett - Sylvie Bauer (Transatlantica)
The Water Cure and Percival Everett by Virgil Russell are two of Percival Everett’s novels that most overtly intertwine literature and the philosophical. They do so not so much by promoting philosophical theories as by putting to the fore that the literary text is a mode of becoming, a gesture of thought. By experimenting with language and form, these two novels participate in the advent of thought and meaning.